Reconstruction of Mandibular Defects - Oliveira, Maiolino Thomaz Fonseca; Rocha, Flaviana Soares; Batista, Jonas Dantas; Moraes, Sylvio Luiz Costa de; Barbosa, Darceny Zanetta- (IntechOpen, 2013)
None